Cancer-Associated Stroke: The Bergen NORSTROKE Study - Henriette Aurora Selvik (Cerebrovascular Diseases Extra, 2015)
Background: Underlying malignancy can cause ischemic stroke in some patients. Mechanisms include the affection of the coagulation cascade, tumor mucin secretion, infections and nonbacterial endocarditis. The release of necrotizing factor and interleukins may cause inflammation of the endothelial lining, creating a prothrombotic surface that triggers thromboembolic events, including stroke. The aims of this study were to assess the occurrence of cancer in patients who had recently suffered an ischemic stroke and to detect possible associations between stroke and cancer subtypes. Methods: All ischemic stroke patients registered in the Norwegian Stroke Research Registry (NORSTROKE) as part of the ongoing Bergen NORSTROKE study were included. Blood samples were obtained on admission. Stroke etiology was determined by the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria, and the severity of stroke was defined according to the National Institute of Health Stroke Scale score. Information about cancer disease after stroke was obtained from patient medical records and The Cancer Registry of Norway. Results: From a total of 1,282 ischemic stroke patients with no history of cancer, 55 (4.3%) patients were diagnosed with cancer after stroke. The median time from stroke onset to cancer diagnosis was 14.0 months (interquartile range 6.2-24.5). Twenty-three (41.8%) patients were diagnosed with cancer within 1 year and 13 (23.6%) within 6 months. The most common cancer type was lung cancer (19.0%). By Cox regression analysis, cancer after stroke was associated with elevated D-dimer levels on admittance (p Conclusions: Cancer-associated stroke is rare, and routine investigation for cancer seems unwarranted in acute ischemic stroke. However, in stroke patients with elevated levels of blood coagulation factors, C-reactive protein, higher age and a history of smoking, underlying malignancy should be considered. Our study suggests that an unknown stroke etiology does not predict malignancy.